Revealing the Moderating Role of Organizational Support in HR Professionals’ Competencies, Willingness, and Effectiveness Relationship: Empirical Evidence From a Developing Economy - Ahmad, Aqeel; Fareed, Muhammad; Isa, Mohd Faizal Mohd; Salleh, Sri Sarah Maznah Mohd (Frontiers in Psychology, 2022)
Human resources management is essential to ensure the success of any organization which is based on the belief that an organization gains competitive advantage by using its people effectively and efficiently. But HR professionals need organizational support to make the employees more committed and passionate about their work. In this study, the researchers aim to examine the moderating effect of organizational support in the relationship between human resource (HR) professionals’ competencies, HR professionals’ willingness, and HR professionals’ effectiveness. HR Professionals’ competencies such as credible activist, talent manager, culture and change steward, strategy architect, business ally, and operational executor nurture HR professionals’ effectiveness. Besides, HR professionals’ willingness is a significant predictor of HR professionals’ effectiveness. To test the relationships, the researcher collected data through survey questionnaire from 183 managers from commercial banks of Pakistan. For statistical analysis, Partial least squares-structural equation modeling (PLS-SEM) is used to analyze the data and test the hypotheses. The findings reveal the positive and significant impact of HR professionals’ competencies and HR professionals’ willingness on HR professionals’ effectiveness. Additionally, the moderating impact of organizational support was also significant among HR professionals’ competencies, HR professionals’ willingness, and HR professionals’ effectiveness relationship. The study contributes in the literature of HR professionals’ effectiveness and organizational support in the banking sector of local context. The study also discusses the implications and future directions. One of them is that the research framework provides guidelines for HR professionals about what competencies are needed to enhance HR professional effectiveness. The present study recommends HR professionals of the banking sector to be involved in strategic planning and implementation in their organization.